The Evaluation of Kurikulum Merdeka Management at Senior High School Mover Ambon City Maluku - Nur Azizah, Wahyuni; Hudallah, Noor; Noekent, Vitradesie (Educational Management, 2022)
The emergence of the COVID-19 pandemic in late December 2019 has significantly impacted the global and Indonesian education systems, resulting in a learning crisis and academic setbacks among students. In response, the government has pursued curriculum innovation, namely the independent curriculum, as a means to recover from the post-pandemic learning crisis. This study aimed to assess the success of the independent curriculum implementation at Senior High School Mover in Kota Ambon. The study focused on the planning, implementation, evaluation, and follow-up stages of the program, analyzing its context, input, process, and product aspects. Data were collected from five high schools and 60 teachers in Ambon City using questionnaires, interviews, and documentation. The findings indicated that the context evaluation of the curriculum emphasized the need for government and school support in terms of adequate funds and facilities. The evaluation of inputs demonstrated that teaching modules were an effective approach in meeting students' needs. The process evaluation revealed that teachers utilized the modules effectively during teaching. This research is expected to provide information about the implementation of independent curriculum in mobilizing high schools, especially in Kota Ambon so that schools can make improvements in the implementation of the kurikulum merdeka.